RNA INTERFERENCE: TOOL FOR GENE SILENCING - DR. SUBHASHREE RAY,; DR. ELLORA DEVI,; DR. ROMA RATTAN, (International Journal of Pharma and Bio Sciences, 2014)
Over the past two decades, dramatic advances in the role of RNA in normal health and disease have been greatly expanded. During development Small RNA molecules regulate eukaryotic gene expression and also during responses to stress including viral infection. RNA interference (RNAi) is a highly conserved process in eukaryotes that leads to post-transcriptional gene silencing through degradation of the target mRNA. This mech- anism is mediated by double-stranded RNA (dsRNA) that is homologous in sequence to the silenced gene. In the recent years various methodologies have been developed to silence specific genes with the help of RNA interference (RNAi) . In this review the cellular pathway of RNAi has been explained along with the recent developments in this field. The role of siRNA in mammalian gene functions with the help of viral and plasmid vector system is described. It has been discovered gene silencing by siRNA using the vectors, activates the interferon response. Hence the future aim is to develop siRNA delivery system to silence genes and use RNAi as a therapeutic module